Cumulative Spine Loading and Clinically Meaningful Declines in Low-Back Function. (February 2014) - Marras, William S.; Ferguson, Sue A.; Lavender, Steven A.; Splittstoesser, Riley E.; Yang, Gang
Objective: The objective was to assess the role of cumulative spine loading measures in the development of a clinically meaningful decline in low-back function. Background: Cumulative spine loading has been a suspected risk factor for low-back pain for many years, yet the measures that characterize risk have not been well delineated. Methods: A total of 56 cumulative exposure measures were collected in a prospective field study of distribution center workers. An individual's risk for a clinically meaningful decline in low-back function (true cases) was explored with daily, weekly, and job tenure cumulative exposure measures using univariate and multivariate statistical modeling techniques. True noncases were individuals with no decline in low-back function. Results: An individual's risk for a clinically meaningful decline in low-back function (true cases) was predicted well versus true noncases (sensitivity/specificity = 72%/73%) using initial low-back function (p(n)), cumulative rest time, cumulative load exposure, job satisfaction, and worker age. Conclusions: Cumulative rest time was identified as an important component for predicting an individual's risk for a clinically meaningful decline in low-back function. Application: This information can be used to assess cumulative spine loading risk and may help establish guidelines to minimize the risk of a clinically meaningful decline in low-back function.